Sosialisasi Profesi Arsitek sebagai Upaya Penguatan Pemahaman Regulasi dan Etika Profesi bagi Generasi Calon Arsitek - Umara Hasmarani Rizqiyah; Husnirrahman J; Firnawati Firnawati; Armiwaty Armiwaty; Raeny Tenriola Idrus (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
This community service program aims to strengthen high school graduates’ understanding of the architectural profession, educational pathways, and legal qualifications required to become a professional architect under the Indonesian Institute of Architects (IAI). The online outreach was held on November 27, 2025, featuring two licensed architects from IAI and attended by 97 participants. The activities included interactive presentations, discussions, and an evaluation through a five-item pretest and post-test. The results show an overall improvement in participants’ comprehension of architects’ roles, responsibilities, and professional legality, with an average accuracy above 90%. The greatest improvement occurred in the legal aspect, where participants recognized the importance of the Surat Tanda Registrasi Arsitek (STRA) as a legal credential for professional practice. This program effectively increased prospective students’ awareness of professionalism, ethics, and regulatory understanding in architectural practice. It also served as an academic promotion platform that bridges architectural education with society’s demand for competent and ethical architects.